THE HEALTH OF THE NATION IS ABOVE AND MOST VALUABLE (World Bulletin of Public Health, 2022)
Health is the main value and basic human need. That is why the head of our state pays special attention to health issues. The main wealth of the nation is its people, and the protection of public health has been and will always be one of the main priorities of Uzbekistan and is constantly in the focus of attention of the President and the Government. According to the Constitution, residents of Uzbekistan have free access to medical care provided through a network of state medical institutions - polyclinics, first aid stations and state hospitals
Keywords: Health; nation